A Comparative Analysis of the Effects of Etomidate and Propofol for Inducing Sedation in Pediatric Patients Undergoing Upper Gastrointestinal Endoscopy - eghbali, ahmad; soloki, khalil; chavoshi, tahereh (Iranian Journal of Pediatric Surgery, 2024)
Introduction: Gastrointestinal endoscopy is a prevalent diagnostic and therapeutic procedure employed for both children and adults. Since Etomidate is a short acting intravenous drug with hemodynamic stability and also it is the choice for sedation and anesthesia among patients afflicted with cardiovascular conditions, we decided to compare the benefits and drawbacks of the mentioned drugs in children undergoing endoscopy. Materials and Methods: For conducting the research, 90 pediatric participants, aged from 1 to 15 years, with ASA I and II class requiring upper gastrointestinal endoscopy (admitted to Mofid Children Hospital) were randomly selected. For 45 patients, intravenous anesthetic drug Propofol (Group P) was administered for sedation required during endoscopy, while in the remaining 45 patients, Etomidate (Group E) was used, and hemodynamic fluctuations, apnea occurrence frequency, sedation recovery length, and nausea and vomiting after sedation were monitored and compared between the two groups. Finally, the data were analyzed using SPSS v.18 software, and t-test and chi-square statistical tests. Results: The average age of the patients was 7.8 ± 7.9 years. The recovery following anesthesia in Group P was 8.3 ± 4.3 minutes, while in Group E, it was 7 ± 3.2 minutes (p=0.373). The reduction in SPO2 levels in Group P was 7.1 ± 3.9%, and in Group E, it was 1.4 ± 0.6% (p=0.01). The variations in heart rate (HR) were 3.9 ± 7.1 in Group P and 0.6 ± 1.4 in Group E (p=0.01). Changes in blood pressure (BP) were 10.1 ± 7.9 mmHg in Group P and 2.7 ± 1.3 mmHg in Group E (p = 0.235). The incidence of apnea was 26.7% (12 individuals) in Group P and 46.7% (21 individuals) in Group E (p=0.02). The occurrence of nausea and vomiting was 4.4% (2 individuals) in Group P and 20% (9 individuals) in Group E (p=0.01). Conclusion: The result of the findings suggests that the patients receiving Etomidate experienced lower saturation drop, and quicker awakening compared to the group of patients receiving Propofol, while the occurrence of apnea, nausea, and vomiting were higher